A Case of Female Acute Urinary Retention Presenting to the ED. (16th August 2017) - Swartzberg, Kylen; Adam, Ahmed; Motara, Feroza; Laher, Abdullah E.
Abstract : Introduction . Acute urinary retention is a rare occurrence in women necessitating further investigation. Potential underlying causes may be broadly classified into obstructive, neurological, pharmacological, and psychogenic categories. Case . A 36-year-old nulliparous female presented to the Emergency Department with a two-day history of acute urinary retention. Point-of-care ultrasonography and CT scan imaging confirmed the presence of a large uterine mass causing compression of the bladder. The acute retention was relieved with urethral catheterization. A Uterine leiomyoma was confirmed on histology after hysterectomy. Discussion . Once the acute urinary retention has been relieved by insertion of a urethral catheter, the underlying cause of the obstruction must be determined. Although uterine leiomyoma is a fairly common finding in the general population, it is an extremely rare cause of acute urinary retention in women with just a handful of reported cases in the literature.